Prevalence of disordered eating and its impact on quality of life among a group of college students in a province of west Turkey Prevalencia de conductas alimentarias de riesgo y su impacto en la calidad de vida de un grupo de estudiantes universitarios en una provincia del oeste de Turquía - Mustafa Tozun; Alaettin Unsal; Unal Ayranci; Gul Arslan (Instituto Nacional de Salud Pública, 2010)
OBJECTIVE: To determine the prevalence of disordered eating (DE) among a group of college students and assess its impact on quality of life. MATERIAL AND METHODS: This study was conducted between December 15th, 2008 and January 15th, 2009 at a Turkish University. Eating Attitudes Test-40 (EAT-40) was used to identify DE. Health Related Quality of Life (HRQoL) was assessed by Medical Outcomes Study Short Form-36. RESULTS: The prevalence of DE was 6.8%. Presence of any physical defect (OR: 2.657), parents living separately (OR: 3.114), mothers having an education level of secondary school and over (OR: 2.583), and families not having social health insurance (OR: 2.603) were important risk factors (f<0.05). CONCLUSIONS: The HRQoL of those with DE was worse than those without it. Periodic screenings should be done to determine DE cases. OBJETIVO: Determinar la prevalencia de conductas alimentarias de riesgo (CAR) entre un grupo de estudiantes universitarios, y evaluar su impacto en la calidad de vida. MATERIAL Y MÉTODOS: Este estudio se realizó entre el 15 de diciembre de 2008 y enero de 2009 en una universidad turca. Se utilizó el Eating Attitudes Test-40 (EAT-40) para identificar CAR. La calidad de vida se evaluó por el estudio de resultados médicos Short Form-36. RESULTADOS: La prevalencia de CAR fue de 6,8%. La presencia de: cualquier defecto físico (RM: 2,657), padres separados (RM: 3,ll4), madre con nivel de educación de escuela de secundaria o más (RM: 2,583), familia sin seguro social (RM: 2,603) fueron importantes factores de riesgo (p<0,05). CONCLUSIONES: La salud y calidad de vida de las personas con CAR fue peor. Se deben hacer exámenes periódicos para determinar casos de CAR.